Controlled delivery of bioactive BDNF for potential treatment of peripheral nerve injury. (November 2020) - Zeng, Wen; Chang, Zhen; Liu, Zhongyang; Zhu, Lei; Wang, Mingbo; Hao, Dingjun; He, Baorong
Abstract: Controlled release of bioactive brain-derived neurotrophic factor (BDNF) via drug delivery system has been showed promise in promoting nerve regeneration after injury. However, some inherited disadvantages limit its application, such as encapsulated protein instability and overdose. In this study, we investigated the potential of chitosan microspheres as an attractive carrier for the controlled release of BDNF. The microspheres were prepared with sodium tripolyphosphate (STPP) by ionic cross-linking. The microspheres showed a spherical shape and relative rough surface morphology as observed by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). The distribution of particle size followed a Gaussian distribution and was not affected by encapsulated protein. The loading content (LC) and encapsulation efficiency (EE) of the microspheres were both affected by the initial amount of BDNF. In vitro release study showed that the release rate of BSA from the microspheres was much faster than that of BDNF. The release profile of the microspheres was over up to 7 days. Weight loss of microspheres after incubation in PBS lasted for 9 weeks. BDNF released from the microspheres was showed to be bioactive, which can be proved by stimulating PC12 cells into a neuronal phenotype in vitro . These data demonstrate that BDNF loaded microspheres offer potential for long-term delivery of bioactive BDNF and could have significant clinical applications for neural tissue regeneration. Highlights: BDNF was encapsulated in the chitosan microspheres by emulsion-ionic cross-linking method. STPP was used as cross-linker. BDNF release profiles from the microspheres were controlled by degradation of both the STPP and chitosan matrix. The released BDNF from the microspheres preserved its biological activity and enhanced PC12 cells differentiation in vitro.